2017
DOI: 10.1007/s00429-017-1558-0
|View full text |Cite
|
Sign up to set email alerts
|

Task-relevant brain networks identified with simultaneous PET/MR imaging of metabolism and connectivity

Abstract: Except for task-specific functional MRI, the vast majority of imaging studies assessed human brain function at resting conditions. However, tracking task-specific neuronal activity yields important insight how the brain responds to stimulation. We specifically investigated changes in glucose metabolism, functional connectivity and white matter microstructure during task performance using several recent methodological advancements. Opening the eyes and right finger tapping had elicited an increased glucose meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 60 publications
3
55
0
Order By: Relevance
“…Our results complement and extend the small number of existing simultaneous BOLD-fMRI/FDG-PET studies reported to date. Consistent with Riedl et al (17) and Wehrl et al (16), we found that blood oxygenation changes in the tissue were related to changes in glucose metabolism in the visual network (however Hahn et al, 2018 (21) found no relationship between glucose metabolism and functional connectivity in the visual and motor cortices using simultaneous BOLD-fMRI/FDG-fPET). Riedl et al (17) showed that local glucose metabolism was highly correlated with BOLD functional connectivity using a simultaneous BOLD-fMRI/FDG-PET with bolus design comparing eyes open versus closed rest, consistent with results obtained in non-simultaneously acquired data (39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results complement and extend the small number of existing simultaneous BOLD-fMRI/FDG-PET studies reported to date. Consistent with Riedl et al (17) and Wehrl et al (16), we found that blood oxygenation changes in the tissue were related to changes in glucose metabolism in the visual network (however Hahn et al, 2018 (21) found no relationship between glucose metabolism and functional connectivity in the visual and motor cortices using simultaneous BOLD-fMRI/FDG-fPET). Riedl et al (17) showed that local glucose metabolism was highly correlated with BOLD functional connectivity using a simultaneous BOLD-fMRI/FDG-PET with bolus design comparing eyes open versus closed rest, consistent with results obtained in non-simultaneously acquired data (39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 89%
“…(39)) which can be very informative but do not allow quantitative inferences to be made. Most existing BOLD-fMRI/FDG-PET studies use a data integration approach, where data from each modality is analysed separately and compared at the second-level using correlation (e.g., (16,21,45,46,48)) or similarity metrics (e.g., (40)). A data integration approach is useful for examining broad relationships between data types, but does not fully capitalise on the shared information between the modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the slow continuous infusion technique, the difference in temporal resolution between FDG-PET and BOLD-fMRI signals represents a significant challenge for designing brain functional experiments that optimise the use of both modalities. One recent study (Hahn et al, 2017) indicate significant neural activity can be simultaneously identified in both imaging modalities (see Figure 2), with a temporal resolution of around 1 min for fPET and 2 s for fMRI .…”
Section: Simultaneous Bold-fmri/fdg-pet Imagingmentioning
confidence: 98%
“…The aim of the fPET approach is to maintain a continuous plasma supply of FDG to provide improved sensitivity of brain-state changes, and better temporal dynamics than bolus PET to track dynamic change of glucose uptake over time. Several studies have demonstrated that fPET can isolate task related changes in glucose uptake (Hahn et al 2016;Hahn et al 2018;Rischka et al 2018;Villien et al 2014;Jamadar, Ward, Carey, et al 2019).…”
Section: Introductionmentioning
confidence: 99%